2020
DOI: 10.1111/dme.14299
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative synthesis of the perceived factors that affect participation in physical activity among children and adolescents with type 1 diabetes

Abstract: AimsTo explore the qualitative literature on the perceived factors, positive and negative, affecting participation by children and adolescents with type 1 diabetes in physical activity, from the perspective of children and adolescents with type 1 diabetes, their family members, teachers or sports coaches, and healthcare professionals.Methods MEDLINE, SPORTDiscus, PsycINFO, CINAHL and Scopus were systematically searched in July 2019. Eligible studies included any that reported qualitative findings on the percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
(104 reference statements)
1
16
0
Order By: Relevance
“…In a qualitative synthesis of factors influencing physical activity among youth with T1DM, Dash et al found that self-management requirements, social support, enjoyment of activities, perceived health benefits, and knowledge of physical activity affected engagement. 38 Interventions to improve physical activity in youth with T1DM have shown significant benefits for A1C and other physical health measures (e.g., body mass index, triglycerides) and small improvements in psychological functioning. 32,[39][40][41][42] In the feasibility and safety evaluation of the present 12-week intervention, participants decreased their systolic blood pressure though there was no improvement in A1C or weight.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative synthesis of factors influencing physical activity among youth with T1DM, Dash et al found that self-management requirements, social support, enjoyment of activities, perceived health benefits, and knowledge of physical activity affected engagement. 38 Interventions to improve physical activity in youth with T1DM have shown significant benefits for A1C and other physical health measures (e.g., body mass index, triglycerides) and small improvements in psychological functioning. 32,[39][40][41][42] In the feasibility and safety evaluation of the present 12-week intervention, participants decreased their systolic blood pressure though there was no improvement in A1C or weight.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) can benefit blood glucose (BG) control, lipid profile, and body composition in children with type 1 diabetes [1,2] but figures suggest these children are less active than their peers [3][4][5][6]. This is potentially influenced by the challenge of managing BG level before, during and after PA, amplified by the spontaneous, often unpredictable and sporadic nature of children's activity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuation in BG level (hypo-and hyperglycaemia) is a side-effect of PA with significant physical symptoms and potential chronic complications [2,9]. Parents of preadolescent children typically take responsibility for diabetes management and find PA a challenge, have concerns about activity-induced hypoglycaemia (fear of hypoglycaemia) [11,12], may avoid intensive PA for their child due to fears [11] and perceive a need for support from healthcare professionals (HCPs) or other experts to help manage these difficulties [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This month we publish eight papers from around the world that used this methodology. In the first, Dash et al [5] have undertaken a systematic review of qualitative literature on the reasons why children and adolescents with type 1 diabetes participate or not in physical activity. As well as individual characteristics, support from friends, family and teachers were key drivers to increase exercise, while the requirement to manage blood glucose during exercise was a major barrier.…”
mentioning
confidence: 99%